Phylogenetic tree analysis of six strawberry (Fragaria spp.) cultivars using dna barcode - Tran Thi, Yen Nhu; Nghi, Khac Nhu; Le, Van Thuc; Tran Thi, Kim Nhu; Trinh, Ngoc Ai (Hue University Journal of Science: Natural Science, 2025)
We performed a phylogenetic analysis of six strawberry cultivars using chloroplast rbcL, rpoC2, and nuclear ribosomal ITS2 sequences. The objectives of this study were to analyze the phylogenetic relationship of 6 strawberry cultivars (Bach Tuyet Trang, Nhat Sky, Ha Lan Hoa Hong, New zealand, Han Goseul and Hana) based on rbcL, rpoC2, and ITS2 regions. The results compared to Nucleotide BLAST GenBank showed a high level of similarity (97.57-99.15%) for the rbcL sequences, 98.40-98.86% for the rpoC2 sequences, and 93.32-99.37% for the ITS2 sequences, all of which were similar to Fragaria x ananassa. Our study indicated that rbcL and nuclear ribosomal ITS2 sequences increased the efficiency of the phylogenetic analysis, while rpoC2 sequences did not provide sufficient clarity to confidently resolve the evolutionary history of strawberry cultivars. Phylogenetic analysis using DNA barcode markers (ITS2, rbcL and rpoC2) through Maximum Parsimony resulted in clades with a high bootstrap value: 99 for HN-HG and bootstrap value of 75 for NZ and HL cultivars. Our findings suggest that DNA barcoding is an efficient tool for identifying the genetic diversity of these six strawberry cultivars and highlights the potential for this study to contribute to the conservation, sustainable genetic resources and breeding program of the Fragaria species.